Znane i nieznane oblicza utopii, antyutopii i dystopii w dziełach światowej kinematografii - Gorączko, Joanna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
In the article „Known and the unknown aspects of utopia, anti-utopia and dystopia in the works of world cinema” examples of movies, in which these types of visions appear, were described. In the paper concepts of utopia, dystopia and anti-utopia were explained. The differences between these notions were presented. The word utopia comes from the book of Thomas More, which presented a vision of an ideal world in which notions of peace and order were realized. On the basis of the concept of utopia, the opposite was built: anti-utopia and dystopia representing an effect of a negative opinion about the surrounding reality. In the article polish and foreign movies, which are good examples of discussed concepts, were presented. Some of these movies were adaptations of the famous literary works, others were original works created solely by the filmmakers.